The influence of affective factors on early foreign language acquisition at elementary level according to the storytelling approach - Jakosz, Mariusz (Glottodidactica, 2018)
he article presents the impact of emotions on teaching children foreign languages. To this end, the results of a research project carried out under the auspices of the Institute of German Philology at the University of Silesia in Katowice are discussed. The project consisted in providing language courses at three kindergartens and one primary school. During those courses, German was taught as a foreign language using the storytelling approach. The project results led to the conclusion that, unlike traditional teaching methods, which are based on very limited input and intensive imitation, the teaching method used creates much more favourable conditions for the activation of innate language acquiring processes and takes the level of the children’s cognitive development into account to a larger degree. The objectives of the evaluation were – among other things – to determine how the storytelling approach affects children’s attitudes to a foreign language, whether it arouses their internal motivation for acquiring a foreign language, whether it contributes to building their confidence, and whether it stimulates their imagination and creativity.